Evaluating the Impact of Community-Based Health Interventions : Evidence from Brazil's Family Health Program - Rocha, Romero; Soares, Rodrigo R. (2012)
This paper analyzes the direct and indirect impacts of Brazil's Family Health Program, using municipality level mortality data from the Brazilian Ministry of Health, and individual level data from the Brazilian household survey. We estimate the effects of the program on mortality and on household behavior related to child labor and schooling, employment of adults, and fertility. We find consistent effects of the program on reductions in mortality throughout the age distribution, but mainly at earlier ages. Municipalities in the poorest regions of the country benefit particularly from the program. For these regions, implementation of the program is also robustly associated with increased labor supply of adults, reduced fertility, and increased school enrollment. Evidence suggests that the Family Health Program is a highly cost-effective tool for improving health in poor areas.